Kant and Kantian Themes in Recent Analytic Philosophy. (7th January 2013) - Howell, Robert
Abstract This article notes six advances in recent analytic Kant research: (1) Strawson's interpretation, which, together with work by Bennett, Sellars, and others, brought renewed attention to Kant through its account of space, time, objects, and the Transcendental Deduction and its sharp criticisms of Kant on causality and idealism; (2) the subsequent investigations of Kantian topics ranging from cognitive science and philosophy of science to mathematics; (3) the detailed work, by a number of scholars, on the Transcendental Deduction; (4) the clearer understanding of transcendental idealism sparked by reactions to Allison's epistemic account; (5) the resulting need—prompted also by new studies of the thing in itself—to face up to the old question of the philosophical defensibility of such idealism; and (6) the active engagement with Kant's ethics and political philosophy that derives from Rawls's and others' work.